2018
DOI: 10.1038/nm.4499
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow niche trafficking of miR-126 controls the self-renewal of leukemia stem cells in chronic myelogenous leukemia

Abstract: Chronic myelogenous leukemia (CML) stem cells (LSCs) are responsible for initiating and maintaining clonal hematopoiesis. These cells persist in the bone marrow (BM) despite effective inhibition of BCR-ABL kinase activity by tyrosine kinase inhibitors (TKIs). Here, we show that although miR-126 supports the quiescence, self-renewal and engraftment capacity of CML LSCs, miR-126 levels are lower in CML LSCs as compared to normal long-term hematopoietic stem cells (LT-HSCs). Down-regulation of miR-126 levels in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
157
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 118 publications
(169 citation statements)
references
References 42 publications
(73 reference statements)
6
157
1
5
Order By: Relevance
“…Interestingly, miR-126-3p levels in our NGS-cohort were lower than those of mi-126-5p, and therefore it was not selected for further validation. However, they were lower in LSC compared to CML HSC and HD HSC (0.59 and 0.35-fold-change, respectively), in agreement with the data reported by Zhang et al 30 . Additionally, the authors showed that miR-126-3p can be transferred from BMderived endothelial cells to primitive hematopoietic cells by extracellular vesicles.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Interestingly, miR-126-3p levels in our NGS-cohort were lower than those of mi-126-5p, and therefore it was not selected for further validation. However, they were lower in LSC compared to CML HSC and HD HSC (0.59 and 0.35-fold-change, respectively), in agreement with the data reported by Zhang et al 30 . Additionally, the authors showed that miR-126-3p can be transferred from BMderived endothelial cells to primitive hematopoietic cells by extracellular vesicles.…”
Section: Discussionsupporting
confidence: 92%
“…However, there are no reports of miR-126-5p in this system 30 . Interestingly, miR-126-3p levels in our NGS-cohort were lower than those of mi-126-5p, and therefore it was not selected for further validation.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…mir-16 family) have been associated with CSC expansion and maintenance 4 . For example, miR-126, which targets CDK3, inhibits qLSC re-entry into cycle but does not induce quiescence and, importantly, it is not acting as a tumor suppressor in AML/CML LSCs 9,10 . Less clear and controversial is the role of miR-221/222/223 in CSC quiescence since their expression is regulated by MSCs in a tumor-and cell type-specific manner but also increases in response to mitogenic stimuli to induce CDK4/CCND1-dependent cell cycle re-entry 4,11 .…”
Section: Mir300 Role In Lscs and Leukemic Progenitors Expression Stumentioning
confidence: 99%
“…Several miRNAs have been associated with CSC expansion and maintenance 4 and PP2A inactivation 8 ; however, a clear causal link between expression of specific miRNAs, persistence of the drug-resistant quiescent CSCs and PP2A loss-of-function is still missing. Furthermore, these miRNAs mostly act as regulators of CSC survival, maintenance into dormancy and cell cycle re-entry but it is unclear whether any of them directly promotes CSC cell cycle exit 4,[9][10][11] .…”
Section: Introductionmentioning
confidence: 99%